2014 IEEE Security and Privacy Workshops 2014
DOI: 10.1109/spw.2014.26
|View full text |Cite
|
Sign up to set email alerts
|

Automatic Identification of Replicated Criminal Websites Using Combined Clustering

Abstract: Abstract-To be successful, cybercriminals must figure out how to scale their scams. They duplicate content on new websites, often staying one step ahead of defenders that shut down past schemes. For some scams, such as phishing and counterfeitgoods shops, the duplicated content remains nearly identical. In others, such as advanced-fee fraud and online Ponzi schemes, the criminal must alter content so that it appears different in order to evade detection by victims and law enforcement. Nevertheless, similaritie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…It has already been mentioned that FS plays a vital role in removing redundant features and building an optimal feature set for evaluation. Drew and Moore () have used two stages using a hierarchical clustering algorithm for recognizing scam websites and their replicates by identifying commonalities in them. Their system is able to identify and group a number of similar websites with substantial accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…It has already been mentioned that FS plays a vital role in removing redundant features and building an optimal feature set for evaluation. Drew and Moore () have used two stages using a hierarchical clustering algorithm for recognizing scam websites and their replicates by identifying commonalities in them. Their system is able to identify and group a number of similar websites with substantial accuracy.…”
Section: Related Workmentioning
confidence: 99%
“…A cross-layer detection model was developed by Xu et al [35], considering both network and application level features. Drew et al [24] investigated the HTML similarities of replicated criminal websites and Cova et al [23] analyzed the phishing websites created by "free" phishing kits. Invernizzi et al [25] proposed the idea of discovering more malicious pages by leveraging the crawling infrastructure of third-party search engines, which is conceptually similar to our method of discovering other domains using the same analytics IDs.…”
Section: Related Workmentioning
confidence: 99%
“…We utilised a number of distinct image file names in the kit's folder structure as markers to identify which websites use the kit. If an aggregator website is observed to have at least 2 of the 3 defined markers, 3 we assume it is running the Gold Coders kit. We found that to be the case for 36 (63.16%) aggregators from the 2013 dataset.…”
Section: E Kit Developersmentioning
confidence: 99%
“…In 2014 Drew and Moore presented a new clustering method that combined features such as HTML tags, textual content and file structure in a weighted manner to try and identify linkages between websites even when criminals were trying to make them look distinct [3]. When applied to 1 216 new HYIP websites from the period January to June 2012 they found 161 clusters of at least size two, plus seven singletons.…”
Section: Related Workmentioning
confidence: 99%